Training On The Development Of Thematic Module At SDN Tanjungrejo 01 Malang - Prihatin Sulistyowati; Dyah Tri Wahyuningtyas (Jurnal Dedikasi, 2021)
The availability of teaching materials that are in accordance with the conditions of students and the learning environment becomes a necessity. These needs can only be met by those who come in direct contact with students in the learning process. Fulfilling the need for teaching materials will help students master learning material. One of the practical teaching materials is a module. Modules become part of the complete set of learning tools. So the teacher also has an obligation to develop teaching materials in the form of modules. The training on the preparation of thematic modules consists of 2 stages, namely the delivery of methods and their systematic preparation and the preparation of draft modules. Through the implementation of training on the preparation of thematic modules, it is able to encourage and improve the skills of teachers to make teaching materials according to the needs of their students. The results of making modules can be used alone and can also be publicized for sale and purchase. It can increase the diversity of teaching materials for the completeness of learning resources.